Identifying factors influencing student's motivation and engagement in course teaching using the e-learning - Shafiin, Nurul Syuhada (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This aim of this concept paper is to provide the readers inputs on the theoretical frameworks that is used by a researcher in exploring factors influence student’s motivation and their engagement in course subject that is teach using the e-learning methods. Through the motivation aspects, the researcher focused on intrinsic and extrinsic factors which influence student’s engagement in the e-learning that been used by a lecturer in teaching subject.